(untitled) (New Jersey, 2003)
This volume is a collection of invited talks, oral contributions and poster contributions devoted to advances in gamma-ray spectroscopy of various capture reactions. In agreement with the trend of previous meetings in the series, the symposium paid special attention to theoretical and experimental studies of nuclear structure at low energies and to nuclear astrophysics. Among the other topics covered are: statistical properties of nuclei and other quantum many-body systems, fundamental physics, nuclear data, practical application of capture reactions, and new techniques and facilities for capture gamma-ray spectroscopy.
Keywords: Nuclear structure,Nuclear astrophysics,Cấu trúc hạt nhân,Thiên thể hạt nhân